Modifikasi Pewarna Alami Ekstrak Etanol Sappan Lignum pada Pewarnaan Soil Transmitted Helminth Pengganti Eosin 2% - Siti Munawaroh; Muh. Shofi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2023)
Worms are a disease that attacks humans in tropical areas. The cause of worm infections in the community is from the Soil Transmitted Helminth (STH) worm group, but the government pays little attention to this. In the process of identifying worm eggs, 2% eosin has been used, which apparently produces waste that is difficult to decompose. Sappan lignum is a natural dye because it contains brizilin which can give a red color, so it can be used as a worm egg dye replacing 2% eosin. This study aims to test whether sappan lignum extract can be used as a dye in fecal examination to detect SHT infections. This research is descriptive research. Examination of worm eggs using the direct feces method was carried out using sappan lignum extract dye with 96% ethanol and 2% eosin as a positive control. This research shows that sappan lignum ethanol extract at a coloring ratio of 1:3 is the best dye compared to other ratios and can be used as a substitute for eosin dye. The conclusion of this research is that sappan lignum ethanol extract can be used as a natural dye in identifying worm eggs.